Seroprevalensi Infeksi Virus Newcastle Disease dan Deteksi Paramyxovirus Pada Itik di Peternakan dan Pasar Unggas di Bali - Purwanda, I GBA; Mahardika, I Gusti Ngurah Kade; Yuniati Kencana, Gusti Ayu (Veterinary Science and Medicine Journal; Vol 3 No 2 (2015), 2015)
Seroprevalence of Newcastle Disease Virus (NDV) infection and the presence of paramyxovirus on ducksat the farmland and the poultry market in Bali have not been known. The purpose of this study was todetermine the comparison of seroprevalence of NDV infection and the presence of paramyxovirus on duckat farmlands and poultry markets in Bali. Locations sampled were Gelgel, Tojan, Akah, Takmung, Tusanvillages in Klungkung Regency, as well as Mengwi, Mengwitani, Lukluk, Sangeh, and Blahkiuh villages ofBadung Regency. The poultry market samples were Galiran of Klungkung Regency, and Bringkit ofBadung Regency. Serum samples and cloacal-tracheal swabs were taken using stratified-random samplingfrom adult ducks of both markets and farmland that had  more than 500 individuals in a flock. Samplingwas carried out every month for 6 months. Antibody against NDV was detected with InhibitionHaemagglutination test (HI). Tracheal and cloacal swabs were propagated in fertile chicken eggs of 9-11days old. Paramyxovirus was detected by the haemagglutination (HA) test and Reverse TranscriptasePolymerase Chain Reaction (RT-PCR). The correlation between NDV seroprevalences at farmland andpoultry markets was analyzed using non-parametric test of Chi-square. The results showed that theseroprevalence of NDV on March until August 2012  reached 45% on farmlands in both regencies, while inthe markets were up to 32.6%. There was no correlation between NDV seroprevalence at farmlands andpoultry markets in the two regencies (r = 0.522, P> 0.05). The paramyxoviruses detected were APMV-5and APMV-8, while NDV was not found.
Keywords: NDV; ducks; seroprevalence; RT-PCR; Paramyxovirus; Poultry Market